Unfolded protein responses in T cell immunity - Zhang, Wencan; Cao, Xu (Frontiers in Immunology, 2025)
Endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) are integral to T cell biology, influencing immune responses and associated diseases. This review explores the interplay between the UPR and T cell immunity, highlighting the role of these cellular processes in T cell activation, differentiation, and function. The UPR, mediated by IRE1, PERK, and ATF6, is crucial for maintaining ER homeostasis and supporting T cell survival under stress. However, the precise mechanisms by which ER stress and the UPR regulate T cell-mediated immunity remain incompletely understood. Emerging evidence suggests that the UPR may be a potential therapeutic target for diseases characterized by T cell dysfunction, such as autoimmune disorders and cancer. Further research is needed to elucidate the complex interactions between ER stress, the UPR, and T cell immunity to develop novel therapeutic strategies for T cell-associated diseases.